Effect of Bio MTA plus & ProRoot MTA pulp capping materials on the regenerative properties of human dental pulp stem cells - Khaled Mohamed Ayoub; Mohamed Mokhtar Nagy; Riham Mohamed Aly; Ghada Nour El Deen; Karim El-Batouty (Scientific Reports)
Abstract The aim of the present study was to investigate the effects of the biological properties of hDPSCs exposed to Bio MTA+ & ProRoot MTA pulp capping materials on the proliferation and odontogenic differentiation of hDPSCs. Human dental pulp stem cells (hDPSCs) were isolated from impacted third molars. Extracts of Bio MTA + and ProRoot MTA were prepared at a 1:1 ratio. The effects of the extracts on hDPSCs cytotoxicity and proliferation were assessed via a CCK-8 assay. Annexin V expression was investigated to assess the effects of both materials on the induction of apoptosis. The effects of ProRoot MTA and Bio MTA + extraction media on the stemness properties of hDPSCs were assessed via real-time quantitative PCR, and the expression of odontogenic markers (RUNX2, DMP1 & DSSP) was analyzed via RT‒PCR Alizarin Red staining. Cells exposed to Bio MTA + had the greatest degree of proliferation. The results of Annexin V staining indicated that Bio MTA + caused the least amount of apoptosis. RUNX2, DMP1 and DSSP were highly expressed by Bio MTA + and indicated successful odontogenic differentiation. Compared with ProRoot MTA, Bio MTA + exhibited an exceptional level of cytocompatibility, as well as advantageous bioactivities, including the preservation of stemness and an increase in the proliferation capacity of hDPSCs. In addition, it demonstrated favorable bioactive properties by stimulating odontogenic differentiation. Bio MTA + offers significant advantages in terms of biocompatibility, bioactivity, and regenerative potential, making it an excellent choice for procedures aimed at preserving or regenerating dental pulp tissue. However, additional research is required to address the lack of in vivo validation, as replicating physiological conditions is crucial for accurately assessing clinical outcomes and comparing them with results obtained from in vitro experiments.